2007
DOI: 10.1021/jp0731452
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of Linear Alcohols by Strong Optical Fields

Abstract: We have experimentally probed the strong-field ionization dynamics of gas-phase linear alcohols, methanol, ethanol, and 1-propanol, by irradiating them with intense, femtosecond-duration laser pulses of 800 and 400 nm wavelength. Specifically, we make high resolution measurements of the energies of electrons that are ionized by the action of the optical field. Our electron spectroscopy measurements enable us to bifurcate the dynamics into multiphoton ionization and tunneling ionization regimes. In the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…25 Therefore, it is more probable that the atomic-like n N orbital is ionized by the VIS/NIR pulse than the π 1 orbital. 26 The yield of immonium dications is a particularly sensitive probe of charge location because the local ionization potential will increase as the hole approaches the amine group causing ionization by the VIS/NIR pulse to be suppressed. It is worth noting that fluctuations in the data close to time zero visible in the inset of Figure 4 might be produced by charge oscillations to and from the amine site with a period close to the duration of the probe pulse (∼6 fs), although this needs to be confirmed by additional experiments with improved statistics.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…25 Therefore, it is more probable that the atomic-like n N orbital is ionized by the VIS/NIR pulse than the π 1 orbital. 26 The yield of immonium dications is a particularly sensitive probe of charge location because the local ionization potential will increase as the hole approaches the amine group causing ionization by the VIS/NIR pulse to be suppressed. It is worth noting that fluctuations in the data close to time zero visible in the inset of Figure 4 might be produced by charge oscillations to and from the amine site with a period close to the duration of the probe pulse (∼6 fs), although this needs to be confirmed by additional experiments with improved statistics.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…The dependence of the tunnel ionization rate on internuclear separation 21 enables the creation of a vibrational wavepacket in the electronic ground state of D 2 using few-cycle pulses. On the other hand, the atomiclike ionization behavior of polyatomics such as alcohols 26 and methyl halides 27 can be attributed to the localization on a single atom of the orbital that is ionized ͑typically the highest occupied molecular orbital͒. 23 For larger molecules, such as linear polyenes 24 and polycyclic aromatic hydrocarbons, 25 measuring their extent of fragmentation as a function of laser intensity and wavelength reveals the importance of nonadiabatic ionization and multielectron effects; these effects are attributed to the presence of spatially delocalized, low-lying electronically excited states in molecules with extensive -conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the time origin of the TOF spectrometer from this calibration with the measured one, we estimated that the error of the energy scale in our data is <5%. The efficacy of our high resolution electron spectroscopy technique to study strong field molecular dynamics has been recently demonstrated [17][18][19]. Further details of the experimental setup and procedure are given elsewhere [20,21].…”
mentioning
confidence: 99%